Meja kot razlika, metafora in diskurz - Kralj, Ana (Teorija in praksa, 2010)
The borders of nation-states, the authors claim, are an embodiment of the junction between the system and life-world. They manifest the translation of the social into physical spaces and vice versa. The authors reflect the meaning of distinctions and oppositions (us and them, here and there, safety and danger, included and excluded etc.) in the construction, maintenance and disappearance of boundaries in space. When it comes to the borders of nation-states distinctions are identified within and grounded solely in the political sphere, the same sphere that needs borders and distinctions in order to constitute itself. A qualitative study about the experience and meaning of the Yugoslav-Slovenian-Italian border lies at the core of the article. Three historical periods are highlighted: the constitution of the border in 1953/54, followed by several decades leading up to Slovenia joining the European Union and the "border disappearance" period after 2004. The authors believe that the field of "absolute politics" dominated over the everyday experiences of the people living in the border area and, when some turning points occurred, demanded radical decisions and identity transformations.
Keywords: Boundaries; Meje; Nacionalna država; National state; Vsakdanje življenje; Everyday life; Etnical identity; Etnična identiteta; državne meje; narodna identiteta